2016
DOI: 10.1016/j.eururo.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Mortality Following Short-term Androgen Deprivation in Clinically Localized Prostate Cancer: An Analysis of RTOG 94-08

Abstract: Background Androgen deprivation therapy (ADT) is associated with coronary heart disease and diabetes in men with prostate cancer (PCa); however, controversy exists regarding ADT and cardiovascular mortality (CVM) with limited data for lower risk disease. Objective We conducted a hypothesis-generating retrospective analysis to evaluate the relationship between short-course ADT and CVM in patients with clinically localized PCa enrolled in a phase 3 trial. Design, setting, and participants A total of 1979 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Cardiovascular mortality was similar in the two groups, as was seen in three previous RTOG phase 3 trials assessing the use or nonuse of androgen-deprivation therapy. 2527 However, only data on cardiac events that were reported as adverse events were collected, which may have introduced an ascertainment bias.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular mortality was similar in the two groups, as was seen in three previous RTOG phase 3 trials assessing the use or nonuse of androgen-deprivation therapy. 2527 However, only data on cardiac events that were reported as adverse events were collected, which may have introduced an ascertainment bias.…”
Section: Discussionmentioning
confidence: 99%
“…1 The observational evidence linking ADT to increased CV risk is substantial (Table 1) Against this, there is evidence from RCTs, from secondary analyses and from a meta-analysis that have failed to identify any increased risk. Confusingly, Jespersen's nationwide cohort study of >30 000 men found an association between ADT and increased risk of MI and stroke.…”
Section: Wwwtrendsinmenshealthcom Trends In Urology and Men's Health mentioning
confidence: 99%
“…In this issue of European Urology, Voog and colleagues [4] update results from the RTOG 9408 trial with a specific focus on cardiovascular mortality. This is a highly clinically relevant study that directly informs the debate on ADT use and potential harms in patients with intermediaterisk disease.…”
mentioning
confidence: 97%